(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Antimicrobial Susceptibility Pattern: The ability of microorganisms to resist the effects of antimicrobial agents, such as antibiotics. Urinary Tract Infection: An infection that occurs in the urinary system, including the kidneys, bladder, and urethra. Escherichia coli: A gram-negative bacterium that commonly causes UTIs, particularly in women. Pseudomonas aeruginosa: An opportunistic pathogen that causes UTIs, especially in patients with compromised immune systems or urinary tract devices. Klebsiella pneumoniae: A gram-negative bacterium known for causing UTIs and producing ESBLs, which confer antibiotic resistance. Enterococcus faecalis: A gram-positive bacterium that can cause UTIs, particularly in people with urinary tract abnormalities or compromised immune systems. Objective(s): The research aimed to explore both the antibiotic resistance patterns among isolated microorganisms in addition to determining which antibiotics provide the best treatment for UTI sufferers. It also investigated both the antibiotic resistance information of isolated microorganisms and the connection between antibiotic prescriptions and UTI patient resistance patterns. Methodology: In this study, bacterial isolates from UTI infections were collected in a clinical setting, and species were identified using common microbiological protocols. Using the disk diffusion method, antibiotic susceptibility and resistance was evaluated by measuring the zone of inhibition. Bacterial species and resistance patterns were compared using statistical techniques such as Chi-Square testing. The therapeutic effect of antibiotics for various isolates was evaluated using descriptive statistics. Results: This study analyzed 200 UTI samples, showing a higher prevalence in females (67.5%) compared to males (32.5%). E. coli was the most common pathogen, with significant antibiotic resistance observed, particularly to FF and Cefipime. Resistance patterns varied across bacterial species, with Pseudomonas showing high resistance to AMC, and Enterococcus having no resistance to SXT and Cipro. Chi-square tests confirmed significant associations between bacterial species and antibiotic resistance, highlighting the need for improved antimicrobial management. Conclusion(s): E. coli was the most prevalent UTI pathogen, especially among females, showing high resistance to key antibiotics like Ciprofloxacin and SXT. The findings stress the importance of improved antimicrobial stewardship and exploring alternative therapies.